Monoprint technique from planographic process made by Cissampelos pareira L. pectin plate. - Inchar, Charyata (Asian Journal of Traditional and Innovative Arts and Textiles, 2022)
The creation pieces of research work are experimental material application in creative research generated from the researcher’s concept to replace gelatin taken from animal body parts used in common planographic process. In the objective toresearch alternative, local-available material to produce plant -based plate to replace gelatin in planographic process. It’s also the experiment and creation of plate printing from planted-based, natural ink Cyclea barbata pectin plate. The research found Khruea-ma-noi or Cyclea barbata or Cyclea barbata Miers or the scientific name Cissampelos pareria L.is alternative, local-available material of which contain good quality to co-produce with natural dye powder and be replaceable with common gelatin plate. Moreover, the plateresolution and definition of the graphic pieces of art works from natural dye ink brough impressive effects in the same level with common gelatin plate. Pectin plate from Cyclea barbata as well in hand process or wrist-weighhand pressing have created unique and fascinating visual element of each leaf, and of other materials used as plates in this creative research. The researcher created planographic arts from Cyclea barbata or Cissampelos pareria L. pectin plate and publicized the creations.